2011
DOI: 10.1177/0218492311411315
|View full text |Cite
|
Sign up to set email alerts
|

Nanofiber-reinforced biological conduit in cardiac surgery: preliminary report

Abstract: Several options are available for right ventricular outflow tract reconstruction, including commercially available bovine jugular vein and cryo-preserved homografts. Homograft non-availability and the problems of commercially available conduits led us to develop indigenously processed bovine jugular vein conduits with competent valves. They were made completely acellular and strengthened by non-conventional cross-linking without disturbing the extracellular matrix, which improved the luminal surface characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The acellular scaffold was coated with electrospun nanofibers of poly-(L) lactic acid (Sigma, St. Louis, MO, USA), polycapronolactone (Sigma, St. Louis, MO, USA), and collagen blend (Sigma, St. Louis, MO, USA). 8 The nanofibers were generated at random to coat the processed muscle sheet. The nanofiber coating was evaluated by scanning electron microscopy, and porosity was also determined.…”
Section: Methodsmentioning
confidence: 99%
“…The acellular scaffold was coated with electrospun nanofibers of poly-(L) lactic acid (Sigma, St. Louis, MO, USA), polycapronolactone (Sigma, St. Louis, MO, USA), and collagen blend (Sigma, St. Louis, MO, USA). 8 The nanofibers were generated at random to coat the processed muscle sheet. The nanofiber coating was evaluated by scanning electron microscopy, and porosity was also determined.…”
Section: Methodsmentioning
confidence: 99%
“…Guhathakurta et al made particular efforts to counteract the aforementioned risks of dilatation, by electrospinning circumferentially oriented nanofibres onto the external surface of decellularized BJVC. The polymeric nanofibres (poly-caprolactone, poly-lactic acid and collagen type I) gave the BJVC extra resistance to dilatation while still keeping it biocompatible ( Guhathakurta et al, 2011 ). In terms of physical reinforcement, the conduit manufacturers actually have more pragmatic solutions.…”
Section: Modified Treatments and Designsmentioning
confidence: 99%
“…Thermal stability, spectroscopy studies of the polymer, and preclinical studies of the coated BJV in animals are in progress to identify the final polymer selection. 59 Flameng and colleagues 60 studied decellularized bovine aortic homografts coated with stromal cell-derived factor-1α and fibronectin, implanted in the RVOT of adolescent sheep. They showed that the coating stimulated reendothelialization and prevented immune responses, conduit calcification, and pannus formation.…”
Section: Tissue-engineered Valves/conduitsmentioning
confidence: 99%